2021
DOI: 10.1002/cpp.2590
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood experiences and repetitive negative thinking in adulthood: A systematic review

Abstract: Background: It has been proposed that repetitive negative thinking (worry and rumination) may be more common among adults who have been exposed to childhood adverse experiences, leading to emotional disorders and other adverse outcomes.The current study aims to present a comprehensive evaluation of the literature examining the relationship between the exposure to childhood adversities, repetitive negative thinking and clinical outcomes in adulthood.Methods: In accordance with Preferred Reporting Items for Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 64 publications
3
27
0
3
Order By: Relevance
“…Cognitive and metacognitive processes may explain why subjects with childhood maltreatment or stressful life events may show emotion dysregulation ( 45 48 ). A growing body of studies suggested that subjects with childhood adversities tend to engage in repetitive negative thinking (e.g., worry and rumination) and dysfunctional metacognitive processes ( 46 , 47 , 49 ), which, in turn, may lead to emotion dysregulation ( 45 , 48 ). Furthermore, according to Hasking's cognition–emotion model theory of NSSI ( 21 ), early life stress may limit the development of emotion regulation strategies, then poor emotion regulation strategies may increase the risk of using NSSI as a form of emotion coping behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive and metacognitive processes may explain why subjects with childhood maltreatment or stressful life events may show emotion dysregulation ( 45 48 ). A growing body of studies suggested that subjects with childhood adversities tend to engage in repetitive negative thinking (e.g., worry and rumination) and dysfunctional metacognitive processes ( 46 , 47 , 49 ), which, in turn, may lead to emotion dysregulation ( 45 , 48 ). Furthermore, according to Hasking's cognition–emotion model theory of NSSI ( 21 ), early life stress may limit the development of emotion regulation strategies, then poor emotion regulation strategies may increase the risk of using NSSI as a form of emotion coping behavior.…”
Section: Discussionmentioning
confidence: 99%
“…What is more, future related research should not be limited to CN, but expand to other types of childhood adversities, such as physical abuse, sexual abuse, family dysfunction, etc. For example, a recent study (75) revealed that childhood adversities was related to negative repetitive thinking (e.g., worry and rumination) in adulthood, while negative repetitive thinking may be related to an increase of depressive symptom severity and suicidal ideation. Therefore, future research may also explore the role of negative repetitive thinking in the association between childhood adversities, ER, and depression/suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Almond and Currie, 2011;Currie and Vogl, 2013). Much of this literature suggests that early life adversity causes neurobiological, somatic, and mental health problems for children and may lead to poor adulthood outcomes, such as impaired mental and physical health (Jones et al, 2018;Lynch et al, 2013;Mersky et al, 2018), higher rates of depression (Mansueto et al, 2021), lower levels of human capital attainment and income (Metzler et al, 2017) and higher rates of crime victimisation (Ports et al, 2016). In China, children who were left behind when one or both parents migrated to the cities to find work have been found to have a lower likelihood of finding a job (Wang et al, 2021), and that the quality of the work when they do find employment is of a lower standard (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%